Wellbeing during Active Surveillance for localised prostate cancer: A systematic review of psychological morbidity and quality of life. Issue 1 (January 2015) - Carter, Gregory; Clover, Kerrie; Britton, Ben; Mitchell, Alex J.; White, Martin; McLeod, Nicholas; Denham, Jim; Lambert, Sylvie D.
Highlights Active Surveillance is recommended for the treatment of localised prostate cancer; however this option may be under-used. We found no adverse impact on psychological wellbeing associated with Active Surveillance treatment. We found no differences in psychological wellbeing when Active Surveillance was compared to active treatments. Patients can be told that Active Surveillance has no increased risk to their psychological wellbeing for consent purposes. Clinicians need not limit access to Active Surveillance based on expectation of adverse impacts on psychological wellbeing.